The fourth way the inspiring future for educational change - Hargreaves, Andy.; Shirley, Dennis, 1955-; Sage eBooks; Ontario Principals' Council; National School Development Council (U.S.) (Thousand Oaks, Calif. ; London : Corwin, 2009)
Beginning with an incisive analysis of the three major educational change efforts of the past 25 years, Andy Hargreaves & Dennis Shirley offer a plan that integrates government policy professional involvement, & public engagement to create an environment of greater inclusiveness, security, & humanity.
Published in association with Ontario Principals' Council and NSDC.
Includes bibliographical references and index.
Specialized.
Description based on print version record.
Keywords: Educational change -- Cross-cultural studies; Comparative education; Education and state -- Cross-cultural studies; Motivation in education -- Cross-cultural studies; Electronic books